Guidelines for Supplies and Assets Management of Schools in Uthai Thani Province Under the Secondary Educational Service Area Office Uthai Thani and Chai Nat - Dachakul, Niti; Wonnawed, Nipon (Vocational Education Central Region Journal, 2025)
The purpose of this research is to study the management of supplies and assets of educational institutions in Uthai Thani Province, under the Uthai Thani Secondary Educational Service Area Office, Chai nat, and to study the guidelines for managing supplies and assets of educational institutions in Uthai Thani Province. Under the jurisdiction of the Uthai Thani Secondary Educational Service Area Office, Chai nat. Sample group used in this research study Educational institution administrators Chief Procurement Officer Procurement officers and teachers under the Uthai Thani Secondary Educational Service Area Office, Chai nat, totaling 241 people. The instrument used for data collection this time was a questionnaire. It is characterized by a 5-level rating scale and group discussion. Statistics used in data analysis are frequency distribution, percentage, mean, and standard deviation. And content analysis. The findings: 1. Management of supplies and assets of secondary educational institutions in Uthai Thani Province Under the jurisdiction of the Uthai Thani Secondary Educational Service Area Office, Chai nat, the overall level is at a high level ( =4.15, S.D.=0.40) arranged by average from highest to lowest, as follows: collecting recording disbursing ( =4.27,S.D.=0.38) maintaining inspectin ( =4.16,S.D.=0.45) borrowing ( =4.12, S.D.=0.50) and distributing supplies ( =4.04, S.D.=0.53). 2. Guidelines for managing supplies and assets of secondary educational institutions in Uthai Thani Province Under the jurisdiction of the Uthai Thani Secondary Educational Service Area Office, Chai nat, there are the following: 1) In terms of storage, recording and disbursement, the procurement officer keeps a current record of the storage of materials and equipment after receiving the materials. 2) In terms of borrowing, the procurement officer prepares a written form for borrowing goods and the school administrator signs it every time the goods are borrowed, and the condition is checked after borrowing. 3) In terms of maintenance and inspection, the school administrators assign the procurement officers to create a manual for the maintenance of procurement, as well as to have the remaining procurement counted and the annual inspection done. 4) In terms of parcel sales, the educational institution sells parcels annually and reports to the Uthai Thani and Chai Nat Secondary Education Area Offices and the Uthai Thani Provincial Audit Office every time.